Innovative Potential as a Factor of Increasing the Competitiveness of the Republic of Tatarstan - Lyubovа Olga; Misbakhova, Albina (Journal of History Culture and Art Research, 2018)
It is generally accepted that oil and gas are the main wealth of Tatarstan, but to maintain the competitiveness of the region, both on the Russian and on the international arenas, not the resources that the region possesses but innovation and its innovative potential come to the fore. The absence of the generally accepted concept of "innovative potential" makes it impossible to determine its rational size, and also distorts the assessment of the influence of innovative potential on the development of the economy. Numerous rating agencies do a regular analysis of the innovative potential of the country and its subjects for monitoring and management purposes. The Republic of Tatarstan takes leading positions in the ratings of innovative regions of Russia and the investment attractiveness of the regions for the last several years. The republic’s leadership focuses on the region’s innovation, on its ability to adapt for changes and generate products of scientific and technological progress, that is an important factor of competitiveness. Tatarstan actively interacts with other regions to create innovative products, new industries and spheres of economic activity. This mutually beneficial cooperation provides the republic with innovative leadership and competitiveness.